Quality improvement in a crisis: a qualitative study of experiences and lessons learned from the Irish National Ambulance Service response to the COVID-19 pandemic. Issue 1 (17th January 2022) - Heffernan, Eithne; Keegan, Dylan; Clarke, Bridget; Deasy, Conor; O'Donnell, Cathal; Crowley, Philip; Hughes, Angela; Murphy, Andrew W; Masterson, Siobhán
Abstract : Objectives: The COVID-19 pandemic has produced radical changes in international health services. In Ireland, the National Ambulance Service established a novel home and community testing service that was central to the national COVID-19 screening programme. This service was overseen by a multidisciplinary response room. This research examined the response room service, particularly areas that performed well and areas requiring improvement, using a quality improvement (QI) framework. Design: This was a qualitative study comprising semi-structured, individual interviews. Maximum variation sampling was used. The data were analysed using an established thematic analysis procedure. The analysis was guided by the framework, which comprised six QI drivers. Setting: Response room employees, including clinicians, dispatchers and administrators, were interviewed via telephone. Results: Leadership for quality: participants valued person-oriented leadership, including regular, open communication and consultation with staff. Person/family engagement: participants endeavoured to provide patient-centred care. Formal patient feedback mechanisms and shared decision-making could be beneficial in the future. Staff engagement: working in a response room could affect well-being, though it also provided networking and learning opportunities. Staff require support and teambuilding. Use of improvement methods: improvements were made in a relatively informal, ad hoc manner. The use of robust methods based on improvement science was not reported. Measurement for quality: data were collected to improve efficiency and accuracy. More rigorous measurement would be beneficial, especially formally collecting stakeholder feedback. Governance for quality: close alignment with collaborators and clear communication with staff are essential. Information and communications technology for quality: this seventh driver was added because the importance of information technology specially designed for pandemics was frequently highlighted. Conclusions: The study provides insights on what worked well and what required improvement in a pandemic response room. It can inform health services, particularly emergency services, in their preparation for additional COVID-19 waves, as well as future crises.